AN ANALYSIS OF STUDENTS' MOTIVATION IN LEARNING ENGLISH - Indi Amelia; Muhammad Anjar Nugraha; Slamet Wahyudi Yulianto (STKIP Siliwangi, 2024)
Students’ motivation is the most important key that has an essential impact on the learning process. This research aimed to find out the motivation that most influences students and explored the students’ perceptions about motivational teaching strategies to boost their motivation to learn English. This research took place at one of the vocational high schools in Indramayu, which consisted of 12 students from the tenth grade as participants. This research used a questionnaire, an interview, and observation to collect the data. The data were analyzed qualitatively using interactive techniques. The results revealed that 3 students (25%) got a higher percentage for extrinsic motivation, while 9 students (75%) got the opposite. It was found that intrinsic motivation has the most influence on students learning English. The results of the interview and observation delineated that the students gave positive responses to the motivational teaching strategies applied by their teacher. Moreover, they think that the teacher was an important factor that succeeded in motivating them to learn English. It is suggested that teachers understand their students’ characteristics before deciding to create and apply certain creative strategies. As a result, teachers may design an effective learning method that encourages students to learn English.